Determination of risk identification process employed by NHS for a PFI hospital project in the UK - Mohamed Ghazali, F. E.; Kabir, Shahid (OmniaScience, 2009)
Long-term concession contracts associated with Private Finance Initiative (PFI) projects, such as National Health Service (NHS) hospitals, are subject to substantial risks, which may not only emerge from project activities such as design and construction, but also from global issues beyond the control of project parties, such as commercial, legal and political risks. Therefore, the principal parties involved must manage risks effectively and efficiently, as early as the project initiation stage, in order to ensure a successful delivery. The aim of this paper is to examine the risk identification process of the NHS PFI hospital in the UK, as a case study, in order to determine the techniques used in risk identification, and their significance, based on estimated probabilities of occurrence. These objectives were achieved through interviews with key personnel within the NHS Trust involved. Results found the sole technique used in risk identification to be brainstorming, through which more than thirty risks were identified and classified under six risk categories: planning, pre-commissioning, design, land purchasing, construction and operation. Thirteen risks were identified as significant based on their estimated probability of occurrence had the project been developed via public procurement. The results of this research will enable public sector clients like the NHS Trust to not only identify the significant risks, which will allow them to focus more attention on developing appropriate mitigation strategies and contingency plans, but also to improve its risk identification process through the use of other techniques in order to support findings from the brainstorming process.